2016
DOI: 10.3390/ma9110923
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial Behavior of Polymer Nanocomposites Based on Polypropylene/Multi-Walled Carbon Nanotubes Fabricated by Means of Ultrasound-Assisted Extrusion

Abstract: Metamaterial behavior of polymer nanocomposites (NCs) based on isotactic polypropylene (iPP) and multi-walled carbon nanotubes (MWCNTs) was investigated based on the observation of a negative dielectric constant (ε′). It is demonstrated that as the dielectric constant switches from negative to positive, the plasma frequency (ωp) depends strongly on the ultrasound-assisted fabrication method, as well as on the melt flow index of the iPP. NCs were fabricated using ultrasound-assisted extrusion methods with 10 wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Nevertheless, MWCNTs diameter is ca. 50 nm as reported previously [14,15]. Thus, the increase of diameter was associated with iPP wrapping onto the MWCNT surface.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, MWCNTs diameter is ca. 50 nm as reported previously [14,15]. Thus, the increase of diameter was associated with iPP wrapping onto the MWCNT surface.…”
Section: Discussionsupporting
confidence: 79%
“…For example, as to the size of agglomerates, the smallest value was found using PP of MFI = 2.5 using variable ultrasound frequency in processing; in this sample, it was found a lower surface/agglomerate ratio and a higher value of electrical charge (1040 V) [51]. A similar study showed that the electrical properties in nanocomposites of PP/ MWCNT with different values of MFI of the polymer matrix depend on the methods used in the ultrasound-assisted extrusion because the ultrasound waves decrease the agglomerates of nanotubes producing conductive materials and static dissipators with a negative dielectric constant [66].…”
Section: Polymer Nanocomposite Focus Of the Study Property Improvemensupporting
confidence: 58%
“…In addition, BaTiO 3 and Al 2 O 3 composites and devices have recently been reported as novel metamaterials [ 34 , 35 , 36 , 37 , 38 ], which can be applied in optical cloaking [ 39 ] and biochemical sensing [ 36 , 40 , 41 , 42 , 43 , 44 ] and detection [ 41 , 42 ], protein analysis [ 45 ], food quality analysis, and telecommunication [ 46 ], etc. They can also be used in tumor treatment, and radar cross-section reduction [ 46 , 47 ] as a therapeutic tool or a polarization conversion device due to their unique dielectric and electromagnetic properties [ 48 ].…”
Section: Introductionmentioning
confidence: 99%